Zhodnocení finanční situace spol. s r. o. Gilose a návrhy na její zlepšení - Gryč, Matěj (Vysoké učení technické v Brně. Fakulta podnikatelská, 2025)
Cílem této bakalářské práce je zhodnotit finanční situaci Gilose s. r. o. a následně formulovat návrhy na zlepšení slabých stránek finančního hospodaření. Při zpracování bakalářské práce jsou použity vybrané metody finanční analýzy, jejíž výsledky slouží jako východisko pro formulování návrhové části.

The propose of this Bachelor thesis is to review the financial situation of the company Gilose s. r. o. and after that to formulate suggestions on how to improve weak points of its financial management. When working on it, selected financial analysis methods had been used and based on the results of it, the suggestion part of the thesis was formulated.
Evaluation of Financial Situation in Gilose, s. r. o. and Proposals to its Improvement
Keywords: Finanční analýza; poměrová analýza; fotovoltaická elektrárna; Financial Analysis; Ratio Analysis; Photovoltaic Power Plant